Ictal kissing: Electroclinical features of an unusual ictal phenomenon. (November 2016) - Özkara, Çiğdem; Taşkıran, Emine; Çarpraz, İrem Yıldırım and Bilir, Erhan and Demir, Aylin Bican and Bora, İbrahim and Aydoğdu, İbrahim and Delil, Şakir and Chassoux, Francine
Highlights: Kissing is a rare ictal phenomena. Mainly related to nondominant temporal lobe. May be seen in seizures involving dominant temporal and extratemporal region. More common among women but may occur in men. The networks involved with the basic innate behavioral patterns may be responsible. Abstract: Purpose: The study aimed to describe the electroclinical features of ictal kissing, an unusual behavior that may occur during focal seizures. Method: Twenty-five patients collected from four epilepsy centers and previously published reports were reviewed for their demographic, clinical, and electrophysiological features. Results: Sixteen of 25 patients were female. The mean age was 32.9 years (9.9–51 years) and the average age at seizure onset was 14.5 years. All seizures were localized to the temporal lobe (TL) and lateralized to right side in 17 patients, left side in 2 patients, and unclear in 6 patients. A total of 55 ictal video electroencephalograms (EEGs) were analyzed. There were other symptoms such as speaking, spitting, hugging, and oral and upper-extremity automatisms along with different types of ictal kissing behavior during the seizures. The median duration of all seizures was 106.7 ± 73.73 s. Kissing occurred at a median time of 71 s (1–95 s) after the onset of seizure, and ictal epileptiform discharges usually involved TL during kissing episode. Conclusion: Ictal kissing is mainly associated with right TL and female gender, although association with left TL may also occurs, possibly related to the circuits involving temporo-insular structures.